Aaron Cooper: capstone - Cooper, Aaron, artist (Colorado State University. Libraries, 2015)
The artist's statement: As a designer, I am a firm believer in creating a bold statement. In order to create a clean design, you must also "un-design," removing any elements that are unnecessary. With design I am able to form an underlying grid, where every element finds itself aligned with another element or shape on the page. I often simplify objects into their most basic elements in order to create an interesting, uncluttered design. I utilize type in a large amount of my work. I enjoy typography as an art as well as a means of communication. By contrasting bold type with thinner alternatives one can lead the viewer's eye throughout the page. Highlighting important information in a contrasting font can create an interesting design element to designate a bold focal point on the page to draw the viewer into the piece. I begin a piece by sketching out some basic layouts by hand. This helps me to get an idea of the best way to align the information in an eye- catching way while remaining legible and easy for the viewer to follow and it also allows me to get out all of my ideas while building off of others. After I have worked out these ideas manually, I bring them to life on the computer. During this process I will often find that my original idea on paper does not perfectly translate when the exact proportions are presented. The layouts are adjusted to the needs of the design. My favorite software is Photoshop because it allows for alignment as well as many tools such as filters and effects in order to achieve the perfect project allowing for endless inspiration and possibilities. When creating my designs I begin with establishing which piece of information should be the focal point of the piece. I then place the other elements on the page asymmetrically aligning with specific points on the focal point, as well as aligning with the other images and text used throughout the piece. I believe that the best designs appear to have their components distributed randomly throughout the page; but one finds that every element is specifically aligned to another found in the piece. My work describes me as an artist as well as a person. As a stubborn perfectionist, my designs reflect my personality by carefully placing components in relation to one another while maintaining an edginess that makes them unique. I have always attempted to add an element of my eccentricity into my work to show a piece of myself through my designs. In something as simple as my magazine spread, although it is extremely precise and technical, I tried to use bold and colorful photos to liven the design and show my personality. However, I believe that a design must ultimately speak for its self to be considered truly successful. If I have done a good job on my work, my personality should be able to shine through the typography and reflect me as a designer.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.